Respostas

2014-01-07T18:27:28-02:00
 x(4x - 1) = 3(x+1)
4x²-x=3x+3
4x²-x-3x-3=0
4x²-4x-3=0
Δ= b²-4ac
Δ=(-4)² -4·4·(-3)
Δ=16+48
Δ=64

x= -b +/- 
√Δ/2a
x= -(-4)+/-√64/2·4
x= 4 +/- 8/8
x'=12/8
x'= 3/2

x''= -4/8
x''= -1/2

Alternativa A. 3/2 = 1,5

3 5 3
2014-01-07T20:57:00-02:00
  x (4x - 1) = 3 (x + 1)
4x² - x = 3x + 3
4x² - x - 3x - 3 = 0
4x² - 4x - 3 = 0
a = 4                 b = - 4                     c = - 3
Δ = b² - 4 . a . c
Δ = (- 4)² - 4 . 4 (- 3)
Δ = 16 + 48
Δ = 64
x = - b ± √Δ
     ---------------
        2 . a
x = - (- 4) ± √64
     ---------------------
            2 . 4
x = 4 ± 8
     --------
         8
x' = 4 + 8 
        8
x' = 12 
÷ 8
x' = 1,5

x" = 4 - 8 
         8
x" = - 4 ÷ 8
x" = - 0,5

S: {1,5; - 0,5}

Resposta: Letra A
4 4 4